Persepsi dan Perilaku Organisasi pada SKPD dalam Pelaksanaan e-Procurement di Kota Magelang - Kurnia Hardjanto; Wing Wahyu Winarno (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2015)
Bad perceptions of conventional procurement of goods and services in government offices, with all of its problems, make some government officials are reluctant to become committee or electronic procurement officials. E-Procurement systems have an impact on organizational behaviour in government procurement of goods and services. This study aims to determine the perception of e-Procurement systems and organizational behaviour changes that occur in the implementation of e-Procurement in Kota Magelang. This research uses survey method, where respondents fill out a questionnaire related to the research variables. Respondents are employees involved in the activities of e-Procurement in Kota Magelang, They are Pejabat Pembuat Komitmen (PPKom), Unit Layanan Pengadaan (ULP) and LPSE staff members, with total respondents are 40 peoples. Six hypotheses are tested using PLS and all of them supported by analysis of data